A retinoid X receptor (RXR)-selective retinoid reveals that RXR-α is potentially a therapeutic target in breast cancer cell lines, and that it potentiates antiproliferative and apoptotic responses to peroxisome proliferator-activated receptor ligands - Crowe, David L (BioMed Central, 2004)
INTRODUCTION: Certain lipids have been shown to be ligands for a subgroup of the nuclear hormone receptor superfamily known as the peroxisome proliferator-activated receptors (PPARs). Ligands for these transcription factors have been used in experimental cancer therapies. PPARs heterodimerize and bind DNA with retinoid X receptors (RXRs), which have homology to other members of the nuclear receptor superfamily. Retinoids have been found to be effective in treating many types of cancer. However, many breast cancers become resistant to the chemotherapeutic effects of these drugs. Recently, RXR-selective ligands were discovered that inhibited proliferation of all-trans retinoic acid resistant breast cancer cells in vitro and caused regression of the disease in animal models. There are few published studies on the efficacy of combined therapy using PPAR and RXR ligands for breast cancer prevention or treatment. METHODS: We determined the effects of selective PPAR and RXR ligands on established human breast cancer cell lines in vitro. RESULTS: PPAR-α and PPAR-γ ligands induced apoptotic and antiproliferative responses in human breast cancer cell lines, respectively, which were associated with specific changes in gene expression. These responses were potentiated by the RXR-selective ligand AGN194204. Interestingly, RXR-α-overexpressing retinoic acid resistant breast cancer cell lines were more sensitive to the effects of the RXR-selective compound. CONCLUSION: RXR-selective retinoids can potentiate the antiproliferative and apoptotic responses of breast cancer cell lines to PPAR ligands.